Methods for determination of antioxidant capacity of traditional and emergent crops of interest in Mexico: An overview (Scientia Agropecuaria, 2024)
Reactive oxygen species are produced by aerobic organisms, including humans, because of metabolism. They can oxidise biomolecules and cause degenerative and cardiovascular diseases (diabetes, atherosclerosis, and neurological damage, among others). However, the consumption of different plant products is related to the prevention of reactive oxygen species–mediated damage because they contain various antioxidants that inhibit the oxidation of biomolecules. Some important natural antioxidants are carotenoids, flavonoids, polyphenols, and vitamins. These molecules are found in various crops produced in Mexico, some of which have been cultivated for a long time, while others have emerged in recent years. The study of the antioxidant capacity of these crops has increased over time. Different methods are used to determine this capacity, depending on the type of antioxidants. In this review, we analyse the antioxidant quantification methods of various crops of interest in Mexico (traditional and emergent), as well as their relationship to prevent the oxidation of biomolecules.